Design of a porous cobalt sulfide nanosheet array on Ni foam from zeolitic imidazolate frameworks as an advanced electrode for supercapacitors. Issue 6 (3rd January 2018) - Han, Xue; Tao, Kai; Wang, Ding; Han, Lei
Abstract : A porous Co9 S8 nanosheet array on Ni foam can be realized via a facile 2D ZIF templated method. Abstract : Porous nanosheet-structured electrode materials are very attractive for the high efficiency storage of electrochemical energy. Herein, a porous cobalt sulfide nanosheet array on Ni foam (Co9 S8 -NSA/NF) is successfully fabricated by a facile method, which involves the uniform growth of 2D Co-based leaf-like zeolitic imidazole frameworks (Co-ZIF-L) on Ni foam followed by subsequent sulfurization with thioacetamide (TAA). Benefiting from the unique porous nanosheet array architecture and conductive substrate, the Co9 S8 -NSA/NF exhibits excellent electrochemical performance with a high capacitance (1098.8 F g −1 at 0.5 A g −1 ), good rate capacity (54.6% retention at 10 A g −1 ) and long-term stability (87.4% retention over 1000 cycles), when acted as a binder-free electrode for supercapacitors. Furthermore, an assembled asymmetric supercapacitor device using the as-fabricated Co9 S8 -NSA as the positive electrode and activated carbon (AC) as the negative electrode also exhibits a high energy density of 20.0 W h kg −1 at a high power density of 828.5 W kg −1 . The method developed here can be extended to the construction of other structured metal (mono or mixed) sulfide electrode materials for more efficient energy storage.